A calculation approach for sandwich panels with facings made of UHPFRC and pre-tensioned CFRP reinforcement. (15th September 2021) - Stark, Alexander; Hegger, Josef
Highlights: Discussion of tests on prestressed sandwich panels under flexural loading using CFRP strands and UHPFRC. Derivation of non-linear calculation approach based on sandwich theory. Discussion of results of validation of proposed model with tests results. Abstract: Sandwich panels are widely applied in construction industry, e.g. for modern building envelopes. They show low self-weight and high load-bearing capacity as well as sufficient physical properties, but are usually limited to relatively short spans. In contrast, thin concrete shell structures show high stiffness as well as load-bearing capacity even for long spans. Combining both construction methods and applying non-corrosive high-strength materials enables multifunctional, light elements with long spans, high load-carrying capacities and additional physical properties. In this paper, sandwich panels with flat and folded plate facings made of ultra-high performance fibre reinforced concrete (UHPFRC) and carbon fibre reinforced polymer (CFRP) prestressing strands are investigated. For a reliable bond strength and to account for spatial facings, a special production method was developed. For the prediction of the flexural behaviour, a new calculation approach is derived step-by-step which accounts for non-linear behaviour. Theoretical bending moment–curvature relationships are derived for UHPFRC cross-sections with CFRP prestressing strands and incorporated in differential equations of sandwich theory to account for cracking and residual stresses in facings. As additional merit of this approach, the tensile strength of UHPFRC is derived from material samples. Spring models to consider stiffness of shear connectors and core material are applied. The non-linear calculation approach covers typical failure mechanisms. Non-linear load-deformation relationships are calculated and compared to experimental test data of prestressed sandwich panels.